Possibilities of the application of fairy tale drawing personality analysis method in kindergarten pedagogical practice (Training and Practice : Journal of Educational Sciences, 2020)
The aim of this study is to determine the application of the fairy tale drawing method to kindergarten pedagogical practice. First, the research emphasizes the special role of fairy tales, listening to stories in early childhood and their important part in personal development. The analysis from the point of view of pedagogical psychology, on the one hand, summarises basic theoretical knowledge and, on the other hand, presents an independent empirical research. Based on the systematic results, it is possible to determine the methodological recommendations that can ensure the efficiency of the implementation of the fairy tale personality cognition process in the field of raising children.